2008
DOI: 10.1071/fp08012
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the gene family encoding acetoacetyl-CoA thiolase in Arabidopsis

Abstract: Thiolases are ubiquitous enzymes involved in many essential biochemical processes. Biosynthetic thiolases, also known as acetoacetyl-CoA thiolases (AACT), catalyse a reversible Claisen-type condensation of two acetyl-CoA molecules to form acetoacetyl-CoA. Here, we report the characterisation of two genes from Arabidopsis thaliana L., ACT1 and ACT2, which encode two closely related AACT isoforms (AACT1 and AACT2, respectively). Transient expression of constructs encoding AACT1 and AACT2 fused to GFP revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
2
28
0
1
Order By: Relevance
“…The 1233 bp AACT coding sequence is predicted to encode a 411 amino acid protein. This size corresponds well with the length of the other predicted AACTs corresponding to the Arabidopsis annotated gene products from At5g47720 and At5g48230: 415 and 403 amino acids, respectively 17.…”
Section: Resultssupporting
confidence: 72%
“…The 1233 bp AACT coding sequence is predicted to encode a 411 amino acid protein. This size corresponds well with the length of the other predicted AACTs corresponding to the Arabidopsis annotated gene products from At5g47720 and At5g48230: 415 and 403 amino acids, respectively 17.…”
Section: Resultssupporting
confidence: 72%
“…It is likely that the H188N mutation masked the S359A phenotype of increased activity (10‐fold) when expressed in vivo because of the limited affinity to AcAc‐CoA, which is only present in submicromolar concentrations in the cytosol. Moreover, the enzyme preceding HMGS, AcAc‐CoA thiolase favours the thiolytic cleavage of AcAc‐CoA to Ac‐CoA in the presence of HS‐CoA (see Ahumada et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…1). Thus, the A. thaliana AACT seems to have dual localisation in both the peroxisome and the cytosol (Carrie et al 2007;Ahumada et al 2008). However, AACT is not restricted to the MVA pathway, and it has been shown that A. thaliana contains two genes AACT1 and AACT2 encoding three and two proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%